Penerapan public relation pada pelayanan UMKM: Studi kasus warung makan sederhana - Rahmawati, Anis Tri (Maliki Interdisciplinary Journal, 2024)
This research discusses the importance of Micro, Small and Medium Enterprises (MSMEs) in Indonesia's economic growth. This research aims to examine the preparation and service stages in managing a simple food stall. This article emphasizes that good public relations within MSMEs also plays a very important role in improving public services. The results of this research show how essential observation, adjustment and collaboration with shop owners are in maintaining efficient operations and customer satisfaction in the MSME business.